Reflections on the demise of First Monday - Frantsvåg, Jan Erik (Nordic Perspectives on Open Science, 2026)
The journal First Monday, an early Open Access journal without article processing charges, announced recently that they would cease publishing with their May 2026 issue, after 30 years of publishing. This calls for some reflections. First Monday has been a well-respected, much-used journal of standing in its field. It has published relatively much over a long period. That such a journal does not see fit to continue publishing is a sign of problems in institution-based publishing, primarily lack of sufficient institutional financial backing for Diamond OA journals.
Keywords: First Monday; Diamond journal; funding; sustainability